Epigenetic therapy combinations in acute myeloid leukemia: what are the options?. (January 2019) - Bewersdorf, Jan Philipp; Shallis, Rory; Stahl, Maximilian; Zeidan, Amer M.
Epigenetics refers to the regulation of gene expression mainly by changes in DNA methylation and modifications of histone proteins without altering the actual DNA sequence. While epigenetic modifications are essential for normal cell differentiation, several driver mutations in leukemic pathogenesis have been identified in genes that affect epigenetic processes, such as DNA methylation and histone acetylation. Several therapeutic options to target epigenetic alterations in acute myeloid leukemia (AML) have been successfully tested in preclinical studies and various drugs have already been approved for use in clinical practice. Among these already approved therapeutics are hypomethylating agents (azacitidine and decitabine) and isocitrate dehydrogenase inhibitors (ivosidenib, enasidenib). Other agents such as bromodomain-containing epigenetic reader proteins and histone methylation (e.g. DOT1L) inhibitors are currently in advanced clinical testing. As several epigenetic therapies have only limited efficacy when used as single agents, combination therapies that target AML pathogenesis at different levels and exploit synergistic mechanisms are also in clinical trials. Combinations of either epigenetic therapies with conventional chemotherapy, different forms of epigenetic therapies, or epigenetic therapies with immunotherapy are showing promising early results. In this review we summarize the underlying pathophysiology and rationale for epigenetically-based combination therapies, review current preclinical and clinical data and discuss the future directions of epigenetic therapy combinations in AML.